PATL2 mutations affect human oocyte maternal mRNA homeostasis and protein interactions in cell cycle regulation - Yin-Li Zhang; Zhanhong Hu; Huifang Jiang; Jiamin Jin; Yan Zhou; Mengru Lai; Peipei Ren; Siya Liu; Ying-Yi Zhang; Yan Rong; Wei Zheng; Shen Zhang; et al. (Cell & Bioscience)
Abstract Background Oocyte maturation defect (OMD) and early embryonic arrest result in female infertility. Previous studies have linked biallelic mutations in the PATL2 gene to OMD, yet the underlying mechanism remains largely unknown. Results This study uncovers three novel mutations (c.1201G > T, c.1284delA and c.1613 + 2_1613 + 3insGT) and three reported mutations (c.1204 C > T, c.1271T > C, c.223 − 14_223-2delCCCTCCTGTTCCA) in the PATL2 gene across five unrelated individuals exhibiting OMD, oocyte death, and early embryonic arrest. RNA sequencing revealed that PATL2 mutations decreased mRNA storage in human germinal vesicle (GV) oocytes and impeded mRNA decay during maturation and in early embryos. We demonstrate that PATL2 interacts with CPEB1 and TUT7 in human oocytes to maintain mRNA homeostasis. Additionally, we observed a reduction in CCNB1 and CCNE1 mRNA levels in PATL2-mutant GV oocytes, which may be linked to GV arrest. Employing both wild-type and mutated PATL2V401F/R402W variants, we characterized the protein interactome of PATL2, identifying disruptions of PATL2V401F/R402W variants predominantly affecting cell cycle-related proteins, including CDC23, APC1 and MAD2L1. PATL2’s interaction with and stabilization of CDC23 in oocytes may elucidate the mechanisms behind the mutation-induced MI arrest. PALT2 is required for the efficient mRNA translation and it maintains the protein level of CDC23, APC1 and MAD2L1 in mouse GV oocyte. Conclusion PATL2 plays a critical role in regulating mRNA accumulation and decay in human oocytes, potentially through interactions with CPEB1 and TUT7, respectively. Mutations in PATL2 lead to oocyte meiosis defects by affecting the mRNA accumulation, mRNA translation, and direct binding to and stabilizing proteins related to cell cycle regulation, such as CCNB1 and CDC23. This study expands the mutational spectrum of PATL2 and provides new insights into the molecular mechanisms underlying PATL2 mutation-associated oocyte maturation disorders.